Plasmid linkage of the D-tagatose 6-phosphate pathway in Streptococcus lactis: effect on lactose and galactose metabolism. - Crow, V L (1983)
The three enzymes of the D-tagatose 6-phosphate pathway (galactose 6-phosphate isomerase, D-tagatose 6-phosphate kinase, and tagatose 1,6-diphosphate aldolase) were absent in lactose-negative (Lac-) derivatives of Streptococcus lactis C10, H1, and 133 grown on galactose. The lactose phosphoenolpyruvate-dependent phosphotransferase system and phospho-beta-galactosidase activities were also absent in Lac- derivatives of strains H1 and 133 and were low (possibly absent) in C10 Lac-. In all three Lac- derivatives, low galactose phosphotransferase system activity was found. On galactose, Lac- derivatives grew more slowly (presumably using the Leloir pathway) than the wild-type strains and accumulated high intracellular concentrations of galactose 6-phosphate (up to 49 mM); no intracellular tagatose 1,6-diphosphate was detected. The data suggest that the Lac phenotype is plasmid linked in the three strains studied, with the evidence being more substantial for strain H1. A Lac- derivative of H1 contained a single plasmid (33 megadaltons) which was absent from the Lac- mutant. We suggest that the genes linked to the lactose plasmid in S. lactis are more numerous than previously envisaged, coding for all of the enzymes involved in lactose metabolism from initial transport to the formation of triose phosphates via the D-tagatose 6-phosphate pathway.